Consumer choice behavior : quality of private sector hospital services - Edirisinghe, K (My University, 2008)
quality of care. The conceptual model was based on three quality dimensions, that of the consumer, the Hospital Manager and the effectiveness of the quality of care. The Consumer aspect was assessed through SERVQUAL service quality model and hospital Managers aspect was assessed through Quality Assurance standards of hospital services. The perception Gap was analyzed aligning with Gap model of service quality. The effectiveness of quality of care was assessed with the aid of six key dimensions of hospital performance measurement of WHO. Taking the overall objective of the study into consideration the questionnaire has been forwarded to both consumer and the Hospital Managers in Western province in Sri Lanka. The questionnaire was forwarded to 100 hospital Mangers and 100 Consumers. It was reveled that Higher Consumer perception of quality of care is positively related to the improvement of the effectiveness of quality of care in Private Hospitals and second hypothesis was also proven, where higher Hospital Managers' perception of quality of care in related to the improvement of the effectiveness of quality of care in Private Hospitals